2016
DOI: 10.1186/s12889-016-3670-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of attitudes toward disability and people with disability among caregivers, the public, and people with disability: findings from a cross-sectional survey

Abstract: BackgroundA negative attitude toward disability is one of the potential barriers for people with disability (PWD) to achieve social equality. Although numerous studies have investigated attitudes toward disability, few have evaluated personal attitudes toward disability among PWD, and made comparisons with attitudes of healthy respondents. This study was to investigate and compare the attitudes of PWD, caregivers, and the public toward disability and PWD in China, to identify discrepancies in attitude among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 28 publications
4
54
2
5
Order By: Relevance
“…Previous studies showed that people with disability had more positive attitudes toward people with disability. 66 In the past years, heightened awareness and increased education about CP has been an integral part of many Canadian pain-related initiatives, including the annual Pain Awareness Week (first week of November put forward by provincial and national organizations such as the Quebec Association for Chronic Pain 45 and the Canadian Pain Coalition 44 ) and knowledge translation initiatives such as the Programme ACCORD. 46 The benefits of population-based campaigns such as the Canadian Back Pain Mass Media Campaign 47 have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that people with disability had more positive attitudes toward people with disability. 66 In the past years, heightened awareness and increased education about CP has been an integral part of many Canadian pain-related initiatives, including the annual Pain Awareness Week (first week of November put forward by provincial and national organizations such as the Quebec Association for Chronic Pain 45 and the Canadian Pain Coalition 44 ) and knowledge translation initiatives such as the Programme ACCORD. 46 The benefits of population-based campaigns such as the Canadian Back Pain Mass Media Campaign 47 have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…BENOMIR, NICOLSON, BEAIL, 2016;ZHENG et al, 2016;HAO et al, 2015) have reported the existence of different attitudes toward workers with disability. To Zheng et al (2016), the negative attitude toward disability is one of the main barriers for individuals with disability reaching for egalitarian opportunities. Benomir, Nicolson and Beail (2016) highlight that the culture and national context contribute for the configuration of such attitudes.…”
Section: Personnel Management Policies and Practicesmentioning
confidence: 99%
“…More recently, some countries, such as the United Kingdom, have come to realize that negative attitudes toward PWDs integration may result in the loss of a relevant potential resource. Because of these negative attitudes, PWDs may end up affected by a lack of work opportunities, low self-esteem, isolation, and illness, which results in great social burden [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%